The Temporal Structure of Patience - Michael R. Kelly (PhaenEx: Journal of Existential and Phenomenological Theory and Culture, 2020)
Abstract This paper presents Anthony Steinbock's broad theory of moral emotions and specifically the distinction he draws between the temporal orientation and the temporal meaning of emotions. The latter distinction is used in order to provide phenomenological descriptions of, and distinctions between, patience and impatience. The paper takes leading clues from Steinbock’s work in an effort to “do” phenomenology in a way that clarifies these specific natural attitude intentionalities.